Risk Factors for the Development of Obstetric Anal Sphincter Injuries in Modern Obstetric Practice. Issue 2 (February 2018) - Ramm, Olga; Woo, Victoria G.; Hung, Yun-Yi; Chen, Hsuan-Chih; Ritterman Weintraub, Miranda L.
Abstract : OBJECTIVE: To characterize the rate of obstetric anal sphincter injuries and identify key risk factors of obstetric anal sphincter injuries, including duration of the second stage of labor. METHODS: This retrospective cohort study included all singleton, term, cephalic vaginal deliveries within Kaiser Permanente Northern California between January 2013 and December 2014 (N=22, 741). Incidence of obstetric anal sphincter injuries, defined as third- or fourth-degree perineal lacerations, was the primary outcome. Multiple logistic regression models were conducted to identify obstetric anal sphincter injury risk factors and high-risk subpopulations. RESULTS: The overall incidence rate of obstetric anal sphincter injuries was 4.9% (3.6% of women who delivered spontaneously vs 24.0% of women who had a vacuum-assisted vaginal delivery, P <.001, CI 18.1–22.6%). In bivariate and multivariate analyses, obstetric anal sphincter injury incidence was higher among women with second stage of labor longer than 2 hours, Asian race, nulliparity, vaginal birth after cesarean delivery, episiotomy, and vacuum delivery. Women with a vacuum-assisted vaginal delivery had four times the odds of obstetric anal sphincter injury (adjusted odds ratio [OR] 4.23, 95% CI 3.59–4.98) and those whose second stage of labor lasted at least 180 minutes vs less than 60 minutes had three times the odds of incurring obstetric anal sphincter injury (adjusted OR 3.20, 95% CI 2.62–3.89). CONCLUSION: Vacuum-assisted vaginal delivery conferred the highest odds of obstetric anal sphincter injury followed by prolonged duration of the second stage of labor, particularly among certain subpopulations. Understanding these risk factors and their complex interactions can inform antepartum and intrapartum decision-making with the goal of reducing obstetric anal sphincter injury incidence. Abstract : Multiple risk factors are associated with obstetric anal sphincter injury, including operative vaginal delivery, length of second stage of labor, and vaginal birth after cesarean delivery.